Comparison of Lignocaine with Ondansetron for Attenuation of Propofol-Induced Pain in Adult Patients Undergoing Laparoscopic Cholecystectomy: Lignocaine Versus Ondansetron for Propofol Pain - Ashfaq, Shumaila; Malik, Maryyam Fayyaz; Asghar, Faheem; Sabir, Sara; Imran, Shahzad; Niazi, Rehan Hassan Khan (Pakistan Journal of Health Sciences, 2025)
Intravenous administration of propofol causes pain that impacts anesthesia procedures. Objective: To compare the efficacy of intravenous Lignocaine and Ondansetron in reducing propofol-induced pain, hemodynamic stability and assess the occurrence of associated adverse effects during induction using a pain scale. Methods: It was a Quasi-Experimental study and conducted for six months from Sep 2024 to Jan 2025 at the Anesthesia department at Islam Medical College, Sialkot. To measure pain effects at laparoscopic cholecystectomy among adult patients. The patients were received 0.5mg/kg Lignocaine through the vein or 8mg Ondansetron before they received propofol treatment. Medical staff evaluated patients’ pain levels on a standard scale while recording their vital signs. Data were analysed by SPSS 21.0. The categorical data was analysed through chi-square and evaluated continuous values with an independent t-test at a significance level of 0.05. Results: Lignocaine brought better pain relief from propofol than Ondansetron at a statistical significance of p < 0.001. People in the Lignocaine group reported 15% of bad pain while 32% of patients in the Ondansetron group felt the same pain level. Ondansetron caused short-lived drops in blood pressure and heart rate but the application of Lignocaine generated mild skin issues. Conclusions: The study proved Lignocaine worked better than Ondansetron at stopping propofol pain effects. Despite its merits Ondansetron still serves as a good treatment option and medical staff should monitor heart-related side effects. Additional medical trials must test the effectiveness of using both drugs together as a pain treatment option.